Barbituric acid-based polyacrylic acid derivatives and preparation methods and applications thereof

By developing a barbituric acid-based polyacrylic acid derivative with water solubility, acid resistance and AIE properties, the problem of difficulty in detecting Fe3+ in water in the prior art is solved, high sensitivity Fe3+ detection is achieved, and the harm to the environment is reduced.

CN116640255BActive Publication Date: 2025-03-28QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310595092.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-23
Publication Date
2025-03-28
Estimated Expiration
2043-05-23

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect the Fe3+ content in water, and traditional methods have potential harm to the environment.

Method used

A barbituric acid-based polyacrylic acid derivative (P-AB) was developed, which has water-soluble, acid resistance and good AIE properties, and can perform fluorescence quenching detection of Fe3+.

Benefits of technology

High sensitivity detection of Fe3+ is achieved, effective response under acidic and alkaline conditions, and reduces environmental harm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116640255B_ABST
    Figure CN116640255B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and relates to a barbituric acid-based polyacrylic acid derivative, a preparation method and an application thereof. The chemical structural formula thereof is as follows: #imgabs0# wherein m=1-100, n=50-400. The barbituric acid-based polyacrylic acid derivative provided by the present invention is water-soluble, has strong acid resistance, has good AIE performance, and has good resistance to Fe 3+ Has good response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a polyacrylic acid derivative based on a barbituric acid group and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Fe 3+ It is one of the most important trace metals in biological systems and is an important component of many biological molecules, such as hemoglobin and myoglobin. 3+ Iron plays an important role in many physiological functions, such as oxygen transport, cell metabolism, enzyme catalysis, and electron transfer. In terms of human health, iron deficiency can lead to anemia and even cirrhosis, while iron excess can lead to anorexia and many age-related diseases. 3+ It is a widely distributed element. If its content is too high, it will cause harm to the environment. 3+ Detection is particularly important. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a barbituric acid-based polyacrylic acid derivative and a preparation method and application thereof. The barbituric acid-based polyacrylic acid derivative provided by the present invention is water-soluble, has strong acid resistance, has good AIE (aggregation-induced emission) performance, and has good Fe 3+ Has good response.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] On the one hand, a barbituric acid-based polyacrylic acid derivative, referred to as P-AB, has a chemical structure as shown below:

[0007]

[0008] Among them, m=1~100, n=50~400.

[0009] On the other hand, a method for preparing the above-mentioned barbituric acid-based polyacrylic acid derivative is obtained by double bond polymerization of monomer BNEA and acrylic acid; the chemical structure of the monomer BNEA is as follows:

[0010]

[0011] A third aspect is the use of the above-mentioned barbituric acid-based polyacrylic acid derivative in fluorescence detection of pH.

[0012] In a fourth aspect, a barbituric acid-based polyacrylic acid derivative is used for fluorescence detection of Fe 3+ Application in.

[0013] A fifth aspect is a method for detecting Fe 3+ The device comprises the above-mentioned barbituric acid-based polyacrylic acid derivative and a fluorescence spectrometer, wherein the fluorescence spectrometer is used to detect the fluorescence after the barbituric acid-based polyacrylic acid derivative is mixed with an aqueous solution to be tested.

[0014] The beneficial effects of the present invention are:

[0015] The barbituric acid-based polyacrylic acid derivative of the present invention contains not only a carboxyl group but also a barbituric acid group. Under acidic conditions, the carboxyl group can form an H bond with the carbonyl group of the barbituric acid part, thereby limiting the rotation and vibration within the fluorophore, thereby generating a strong fluorescence intensity; under alkaline conditions, the hydrogen bond between the carboxyl group and the fluorophore is destroyed, and the excited state may dissipate energy through non-radiative methods such as rotation and vibration, resulting in a weakened fluorescence intensity, thereby realizing fluorescence detection of pH. In addition, due to the Fe 3+ It is easy to combine with -COOH, inhibiting the H bond formation between the carboxyl group and the carbonyl group of the barbituric acid part, thereby significantly reducing the fluorescence intensity of the barbituric acid-based polyacrylic acid derivative in aqueous solution, achieving Fe 3+ Quench its fluorescence. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0017] Figure 1 For the embodiment of the present invention 1 H NMR spectrum, A is BNEA, B is acrylic acid, and C is P-AB;

[0018] Figure 2 FT-IR spectra of the embodiments of the present invention, (a) is PAA, (b) is BNEA, and (c) is P-AB;

[0019] Figure 3 The UV-visible spectra of M4, BNEA and P-AB in different solutions in the embodiment of the present invention are shown;

[0020] Figure 4The test results of the AIE performance of P-AB in the embodiment of the present invention are shown in Figure 1, where A is the fluorescence spectrum of P-AB in a mixed solution (H2O-THF), and B is the change in maximum fluorescence intensity (λex = 550 nm, CP-AB = 30 mg / L);

[0021] Figure 5 Figures 1 and 2 are fluorescence results of P-AB aqueous solutions of different concentrations in the embodiments of the present invention, A is the fluorescence spectrum of P-AB (λex=550nm), and B is the curve of the maximum fluorescence intensity of P-AB in aqueous solution changing with the concentration gradient;

[0022] Figure 6 Figure 1 is a fluorescence result diagram of P-AB in water-glycerol mixtures of different proportions in the embodiment of the present invention, A is the fluorescence spectrum of P-AB in the mixed solution (H2O-glycerol), and B is the change curve of the maximum fluorescence intensity, (λex = 550nm, CP-AB = 30mg / L);

[0023] Figure 7 TEM images of P-AB in two different mixed solutions (H2O-THF) according to the present invention, A is H2O:THF=7:3, B is H2O:THF=3:7;

[0024] Figure 8 (A) Fluorescence spectra and (B) maximum fluorescence intensity changes of P-AB at different pH values ​​in the embodiments of the present invention (λex = 550 nm, CP-AB = 30 mg / L);

[0025] Fig. 9 : is the UV spectrum of P-AB in water at different pH values ​​in the embodiment of the present invention;

[0026] Fig.10 TEM images of P-AB in aqueous solutions of different pH values ​​(A: pH=3, B: pH=12) according to the present invention;

[0027] Fig.11 In the embodiment of the present invention, HCl solution ([H + ]=0.5M) and NaOH solution ([OH - ]=0.5M) after P-AB (CP-AB=30mg / L) in aqueous solution;

[0028] Fig.12 Figure 2 is the fluorescence result of P-AB in acidic and alkaline solutions with different ratios of water to tetrahydrofuran in the embodiment of the present invention, A is an acidic solution ([H + ]=0.5mM) in water and tetrahydrofuran ratio, B is the acidic solution ([H +]=0.5mM) in the maximum fluorescence intensity curve as a function of the ratio of water to tetrahydrofuran, C is an acidic solution ([OH - ]=0.5mM) in water and tetrahydrofuran ratio, D is the acidic solution ([OH - ]=0.5mM), λex=550nm, CP-AB=30mg / L;

[0029] Fig.13 The fluorescence mechanism diagram of P-AB in acidic and alkaline solutions in the embodiment of the present invention;

[0030] Fig.14 In the embodiment of the present invention, Fe 3+ (A) Fluorescence spectra and (B) maximum fluorescence intensity plots of P-AB under gradient concentrations (λ ex =550nm,C P-AB =30mg / L);

[0031] Fig.15 P-AB detection of Fe in the embodiment of the present invention 3+ Complexation mechanism diagram;

[0032] Fig.16 In the embodiment of the present invention, P-AB and Fe 3+ (A) Fluorescence spectra and (B) maximum fluorescence intensity changes (λ ex =550nm,C P-AB =30mg / L, [Fe 3+ ]=0.1mM);

[0033] Fig.17 Comparison of (A) fluorescence spectra and (B) maximum fluorescence intensities of P-AB in aqueous solutions of different cations ([cation] = 0.1 mM) according to the present invention (λ ex =550nm,C P-AB =30mg / L);

[0034] Fig.18 P-AB to Fe in the embodiment of the present invention 3+ Detection limit (λex=550nm,C P-AB =30mg / L);

[0035] Fig.19 The P-AB method for detecting Fe in the embodiment of the present invention 3+ (A) Fluorescence spectrum and (B) maximum fluorescence intensity bar graph (λ ex =550nm, C P-AB =30 mg / L, [cation] = 0.1 mM);

[0036] Fig. 20 In the embodiment of the present invention, P-AB and Fe 3+ At different pH (λ ex =550nm,

[0037] C P-AB =30mg / L,C Fe3+ =0.1 mM) aqueous solution (A) fluorescence spectrum and (B) maximum fluorescence intensity change;

[0038] Fig.21 The fluorescence stability of (A) P-AB in aqueous solution and (B) Fe 3+ Response time detection. DETAILED DESCRIPTION

[0039] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0040] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0041] The purpose of the present invention is to provide a novel barbituric acid-based polyacrylic acid derivative. After research, it is found that the novel barbituric acid-based polyacrylic acid derivative has water solubility, strong acid resistance, good AIE performance, and is effective for Fe 3+ Has good response.

[0042] A typical embodiment of the present invention provides a barbituric acid-based polyacrylic acid derivative, referred to as P-AB, whose chemical structure is as follows:

[0043]

[0044] Among them, m=1~100, n=50~400.

[0045] In some embodiments, m:n=1:2-10, preferably, m:n=1:4-8.

[0046] In some embodiments, the weight average molecular weight is (1.0-5.0)×10 4 .

[0047] Another embodiment of the present invention provides a method for preparing the above-mentioned barbituric acid-based polyacrylic acid derivative, which is obtained by double bond polymerization of monomer BNEA and acrylic acid; the chemical structure of the monomer BNEA is as follows:

[0048]

[0049] In some embodiments, the molar ratio of the monomer BNEA to acrylic acid is 1:2-10, preferably 1:4-8.

[0050] In some embodiments, the initiator used in the double bond polymerization reaction is azobisisobutyronitrile (AIBN).

[0051] In some embodiments, the double bond polymerization reaction is carried out under the conditions of heating to 65-80° C. in an inert atmosphere.

[0052] In some embodiments, the preparation process of monomer BNEA is as follows: protecting the hydroxyl group on 2-(N-ethyl(phenyl)amino)ethanol with acetic anhydride to obtain intermediate M1; performing Vilsmeier-Haack reaction on intermediate M1 to obtain intermediate M2; then performing deacetylation protecting group reaction to prepare intermediate M3; using triethylamine as an acid binder, reacting intermediate M3 with acryloyl chloride to obtain intermediate M4; and condensing intermediate M4 with barbituric acid to obtain monomer BNEA.

[0053] The reaction process is as follows:

[0054]

[0055] A third embodiment of the present invention provides an application of the barbituric acid-based polyacrylic acid derivative in fluorescence detection of pH.

[0056] Specifically, a barbituric acid-based polyacrylic acid derivative is added to a test aqueous solution for fluorescence detection.

[0057] A fourth embodiment of the present invention provides a method for detecting Fe in a fluorescent manner using the barbituric acid-based polyacrylic acid derivative. 3+ Application in.

[0058] Specifically, fluorescence detection of Fe 3+ When the pH value of the solution is not higher than 11, the detection effect is better under this condition.

[0059] A fifth embodiment of the present invention provides a method for detecting Fe 3+The device comprises the above-mentioned barbituric acid-based polyacrylic acid derivative and a fluorescence spectrometer, wherein the fluorescence spectrometer is used to detect the fluorescence after the barbituric acid-based polyacrylic acid derivative is mixed with an aqueous solution to be tested.

[0060] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0061] Example

[0062] Materials and Apparatus:

[0063] All materials used were commercially available and used without any further purification unless otherwise stated. 2-(N-ethyl(phenyl)amino)ethanol, barbituric acid, acrylic acid (AA), phosphorus oxychloride (POCl3), azobisisobutyronitrile (AIBN), pyridine, acetic anhydride (Ac2O). N,N-dimethylformamide (DMF), ethanol and triethylamine were dried according to standard methods. All materials were from MacLean (Shanghai MacLean Biochemical Technology Co., Ltd.). The water used during the experiments was ultrapure water.

[0064] 1H NMR spectra were measured using an AVANCZ II 400 spectrometer (Bruker, Karlsruhe, Germany) with DMSO-d6 as solvent. Chemical shifts are reported in parts per million (ppm) and referenced to residual solvent peaks (DMSO-d6: 1H = 2.5 ppm and H2O: 1H = 3.4 ppm). UV-visible absorption spectra were measured using a TU-1810 UV-visible spectrophotometer (Puxi General Instrument Co., Ltd., Beijing, China). Photoluminescence emission spectra were measured using a Hitachi F-2710 fluorescence spectrometer (Hitachi High-Tech, Tokyo, Japan). Infrared spectra were obtained using a Nicolet iS20 Fourier transform infrared spectrometer (Thermo Fluorescence Technology (Beijing) Co., LTD). TEM images were obtained using a transmission electron microscope (JEOL JEM 2100, Japan). High-resolution mass spectra (ESI) were measured using a Thermo Scientific Q Exactive modular quadrupole orbitrap mass spectrometer (Brukerauto fluorescence ex maX MALDI-TOF (TOF), Germany).

[0065] Synthesis of barbituric acid-based polyacrylic acid derivatives (P-AB):

[0066] The synthetic route is as follows:

[0067]

[0068] The specific steps are as follows:

[0069] A mixture of 2-(N-ethyl(phenyl)amino)ethanol (5 g), acetic anhydride (16 g) and pyridine (7 g) was stirred at 90°C for 24 hours, cooled to room temperature, and then washed with water (20 mL). The mixture was extracted with ethyl acetate and the organic phase was washed twice with water. The yellow solution was dried over anhydrous MgSO4 overnight, and then the solvent was removed to obtain intermediate M1.

[0070] Intermediate M1 (5 g) was added to DMF (5 mL). POCl3 (4 g) was added dropwise to the dark green oil at 0°C and stirred vigorously. The dark green oil was stirred at 0°C for 40 min. The mixture was slowly raised to room temperature, maintained for 20 min, and then stirred at 90°C for 3 h to obtain a dark green solution. Ice water (20 mL) was added and the pH was adjusted to 6-8 with a saturated Na2CO3 solution. The solvent was removed, vacuum dried, and the green precipitate, i.e., intermediate M2, was collected. 1 H NMR (400 MHz, DMSO-d 6 )δ9.65(s,1H),7.67(d,J=8.6Hz,2H),6.83(d,J=8.7Hz,2H),4.18(t,J=5.9Hz,2H),3.65(t,J=5.9Hz,2H),3.48(q,J=7.0Hz,2H),1.98(s,3H)and 1.11(t,J=7.0Hz,3H).

[0071] A green mixture of intermediate M2 (2 g) ethanol (20 ml) and NaOH (1.5 g) water (10 ml) was stirred at 25 ° C for 7 hours, and then the pH was adjusted to 8-9 with a diluted HCl solution. The ethanol and water were removed and the residual solid was dissolved in ethyl acetate (50 mL). The mixture was filtered and the solvent in the filtrate was evaporated. The yellow viscous solution was collected by filtration and then dried in a vacuum to obtain intermediate M3. 1 H NMR (400 MHz, DMSO-d 6 )δ9.63(s,1H),7.65(d,J=8.5Hz,2H),6.78(d,J=8.8Hz,2H),4.83(t,J=5.4Hz,1H),3.57(q,J=5.9Hz,2H),3.49–3.46(m,2H),3.46–3.43(m,2H)and 1.10(t,J=7.0Hz,3H).

[0072] Dissolve intermediate M3 (0.3 g) in dry dichloromethane (1.0 mL). At 0°C, add triethylamine (41.8 μL) and acryloyl chloride (16.2 mL) dropwise. Then stir at room temperature for 3 hours, wash the mixture with water (20 mL), and extract with ethyl acetate (50 mL). Evaporate the organic phase solvent, and purify the yellow viscous solution by column chromatography on silica gel using a mixture of ethyl acetate and petroleum (1:2) as the eluent to obtain a yellow viscous solution, namely intermediate M4. 1 H NMR (400 MHz, DMSO-d 6 )δ9.66(s,1H),7.70–7.65(m,2H),6.90–6.84(m,2H),6.31(dd,J=17.3,1.5Hz,1H),6.15(dd,J=17.3,10.4Hz,1H),5.9 5(dd,J=10.4,1.5Hz,1H),4.30(t,J=5.8Hz,2H),3.72(t,J=5.8Hz,2H),3.50(q,J=7.0Hz,2H)and1.12(t,J=7.0Hz,3H).

[0073] In ethanol (20 mL), add intermediate M4 (1 g) and barbituric acid (1 g) in a 100 mL three-necked flask. Stir at 80°C for 4 h. After the reaction is completed, cool it for a while and filter it under reduced pressure to generate a light yellow product, namely BNEA monomer. 1 H NMR (400 MHz, DMSO-d 6 )δ11.09(d,J=2.1Hz,1H),10.96(d,J=2.0Hz,1H),8.42(d,J=9.2Hz,2H),8.15(s,1H),6.87(d,J=9.0Hz,2H),6.31(dd,J=17.3,1.5Hz,1H),6.15(d d,J=17.3,10.4Hz,1H),5.95(dd,J=10.4,1.5Hz,1H),4.33(t,J=5.7Hz,2H),3.79(d,J=11.4Hz,2H),3.56(q,J=7.0Hz,2H),1.15(t,J=7.0Hz,3H). 13 C NMR (101 MHz, DMSO-d 6 )δ

[0074] 165.95,165.22,163.26,155.84,153.06,150.84,139.73,132.60,128.56,120.70,111.79,110.40,62.13,48.57,45.50,12.55.

[0075] BNEA monomer (1.785g) was dissolved in dry DMF (20ml). Acrylic acid (2.16g) and AIBN (50mg) were added to a three-necked flask. Stirred for 24h under nitrogen protection at 70℃ to obtain a viscous purple-red solution. The solution was placed in a dialysis bag and dialyzed with water as the dialysate until the dialysate had no obvious color change. Then, anhydrous ethanol was used as the dialysate for dialyzation until the color of the dialysate did not change. A purple-red liquid was obtained and poured into a culture dish. Dry at room temperature to obtain a purple solid film, namely the P-AB membrane. 1 H NMR (400 MHz, DMSO-d 6 )δ12.25(s,57H),9.65(s,1H),7.68(d,J=8.4Hz,2H),6.85(d,J=8.6Hz,2H),2.27–2.11(m,49H),1.75(s,22H),1.51(s,76H).

[0076] The polymer P-AB is soluble in water and most organic solvents, such as DMF, methanol, dichloromethane and DMSO, but insoluble in THF. The molecular weight and polydispersity index of the polymer were determined by gel permeation chromatography (GPC). n ) is 2.316×10 4 , weight average molecular weight (M w ) is 2.800×10 4 , the polydispersity index (PDI) is 1.209.

[0077] Determination of molecular structure:

[0078] use 1 H NMR, 13 The molecular structure of BNEA was determined by C NMR, IR (infrared) spectroscopy and HRMS (high resolution mass spectrometry). 1 The molecular structure of the polymer was determined by H NMR and IR spectra. 1 H NMR spectra of its monomers 1 H NMR spectra were compared with those in DMSO-d 6 All the BNEA, acrylic acid (AA) and P-AB 1 HNMR spectrum. Figure 1 In A, the H atom peaks of carbon a (Ca) and carbon c (Cc) appear at 6.1 and 8.1 ppm, and the characteristic chemical shifts of H atoms of phenyl (Cb) appear at 6.8 and 8.4 ppm. Another characteristic peak of NH (d) is 11 ppm. Figure 1In C, the peaks at 6.8 and 7.7 ppm are still retained, indicating the presence of phenyl groups in polymer P-AB. The peak of Cc shifts from 8.1 ppm to 9.6 ppm, and the peak of NH disappears, which may be due to the dialysis of the polymer in aqueous solution. 36 However, no peak around 6.1 ppm was found in 1C, indicating that there is no double bond (Ca) in P-AB. 1 H NMR characteristics confirmed that the monomer BNEA had been incorporated into the polymer P-AB. Figure 1 In B, it can be found that the H in the carboxyl group has a peak at 12ppm and also appears at the same ppm. Figure 1 C. This result proves that monomer AA can also be polymerized into polymer P-AB. 1 The HNMR results all showed that the polymer P-AB was successfully synthesized.

[0079] like Figure 2 As shown, both P-AB and BNEA have absorption peaks of CH stretching vibration of benzene ring at υ≈3000cm-1. In addition, both P-AB and BNEA have absorption peaks of C=O stretching vibration at filling factor υ=1630cm-1. This proves that BNEA is polymerized into P-AB. In addition, the infrared spectra of P-AB, BNEA and PAA show a significant peak at υ=1730cm-1, which may be the C=O stretching vibration of the ester group. This confirms that PAA is the basic component of P-AB. The above infrared data all prove the successful synthesis of P-AB.

[0080] Fluorescence phenomenon and microscopic morphology of P-AB at different ratios of water to tetrahydrofuran:

[0081] BNEA is the fluorophore of P-AB. It is soluble in most organic solvents but insoluble in water. However, the polymer P-AB becomes insoluble in most organic solvents but soluble in water. This huge change in solubility is due to the presence of a large number of hydrophilic carboxylic acid groups in P-AB. Figure 3In the graph, M4 exhibits an absorption peak at 350 nm, which may be due to a localized π-π* transition around the phenyl group. BNEA is a typical D-π-A molecule, whose electron donor is a dialkylamine group and the electron acceptor is barbituric acid. In pure THF solvent, there is a strong absorption peak at 450 nm (curve 'BNEA(0)'), which may be related to the intramolecular charge transfer from the electron donor to the acceptor. However, when the solvent is changed to THF-H2O containing 90% H2O, a new peak appears at 350 nm. At longer wavelengths, the peak red-shifts from 450 nm to 500 nm (see curve 'BNEA(90)'). For D-π-A molecules, the twisted intramolecular charge transfer (TICT) mechanism usually occurs in highly polar media such as water. It can be seen that the BNEA molecule is severely twisted in THF-H2O, and a localized π-π* transition occurs around the phenyl group at 350 nm, corresponding to the absorption of M4. In addition, in more polar solvents, the excited state energy level is lowered, resulting in a red shift in absorption from 450nm to 500nm.

[0082] The UV-visible absorption spectrum of P-AB in water shows a strong absorption peak at 350nm and a weak absorption peak at 570nm (see curve 'P-AB (100)'). Based on the above analysis of the absorption spectra of M4 and BNEA, we believe that the absorption peak at 350nm represents the benzene ring and the absorption peak at 570nm represents the fluorophore of the barbituric acid group on the polymer chain. Compared with BNEA, P-AB shows a stronger red-shifted absorption at 570nm in THF-H2O containing 90% H2O, which may be due to the large amount of -COOH polarizing the medium in P-AB.

[0083] The AIE properties of P-AB were determined using water as a good solvent and tetrahydrofuran as a poor solvent. The fluorescence spectra were recorded as the proportion of tetrahydrofuran in the water-tetrahydrofuran mixed solvent increased. Figure 4 A and Figure 4 B shows that as the THF ratio increases from 0 to 60%, the fluorescence intensity gradually increases. This result indicates that P-AB has an AIE phenomenon. When THF is greater than 60%, the fluorescence intensity decreases slightly. This is most likely caused by the polymer falling from the solution.

[0084] Changing the fluorescence of P-AB concentration in aqueous solution, such as Figure 5 As shown in the figure, as the P-AB concentration increases from 10 mg / L to 100 mg / L, the fluorescence intensity gradually increases. The fluorescence intensity shows a good linear relationship, indicating that the ACQ phenomenon does not occur at high concentrations.

[0085] The fluorescence of P-AB in water-glycerol mixtures with different ratios is shown in Figure 2. Figure 6As shown, the fluorescence intensity of P-AB increases with the increase of glycerol ratio, which further confirms the AIE property of P-AB.

[0086] The microstructure of P-AB in water-THF mixtures with different ratios was studied by transmission electron microscopy (TEM). Figure 7 As shown in A, when the ratio of H2O to THF is 7:3, a chain conformation appears. When the ratio of the mixed solvent (H2O:THF) is 3:7, a microsphere conformation is formed ( Figure 7 B). Apparently, in a good solvent with a low THF ratio, the polymer chains are loose and flexible, forming a chain-like conformation. As the amount of THF increases, the solubility of the polymer decreases, leading to the aggregation of the chains, forming a globular conformation. In addition, a large number of carboxylic acid groups in the polymer form hydrogen bonds with the fluorophore. The rotation and vibration within the fluorophore are restricted.

[0087] Fluorescence phenomenon and microscopic morphology of P-AB at different pH values:

[0088] Since the polymer contains a large number of carboxylic acid groups, the pH value of the medium has a great influence on the fluorescence and microscopic morphology of P-AB. The fluorescence spectrum of P-AB was measured in an aqueous medium with a pH of 2 to 11 (CP-AB = 30 mg / L). Figure 8 As shown. At pH = 2, the polymer P-AB exhibits a higher fluorescence intensity. When the pH increases from 2 to 11, the fluorescence intensity decreases significantly ( Figure 8 B). We believe that in acidic solutions, the large amount of -COOH on the polymer chain leads to a large number of H bonds within or within the polymer chain, which may restrict the rotation or vibration of the fluorescent group, resulting in strong emission. On the other hand, the solubility of P-AB in alkaline aqueous solution is greatly improved due to the conversion of COOH to COO-. In addition, the large amount of COO- on the polymer chain may lead to strong electrostatic repulsion between or within the polymer chain. Therefore, the polymer chain is loose in alkaline aqueous solution, which allows the fluorophore to rotate or vibrate more freely inside, resulting in weaker fluorescence intensity.

[0089] The UV-visible spectra of P-AB under acidic, neutral and alkaline conditions are shown in Figure 2. Fig. 9 As shown. When the pH is 2 and 7, the two absorption peaks are almost the same, both appearing at around 575nm. When the pH is 12, the absorption peak blue-shifts to 545nm, and the absorption peak intensity decreases. Under acidic and neutral conditions, hydrogen bonds can be formed between or within polymer chains, and the interaction between fluorophores is enhanced. Under alkaline conditions, hydrogen bonds cannot be formed, resulting in a blue shift in the longest absorption wavelength.

[0090] When the medium changes from acidic to alkaline, the microstructure of P-AB changes significantly. Fig.10TEM images of polymer P-AB in aqueous solution at different pH values ​​(A: pH = 3; B: pH = 12). It can be observed that when pH = 3, the microscopic morphology of P-AB is cubic and other granular, which may be due to the formation of a large number of h bonds between or within the polymer chains by COOH, causing the polymers to aggregate tightly. When pH = 12, the TEM image of P-AB shows an amorphous structure. This may be due to the loose aggregation of polymer chains under alkaline conditions. The trend of micromorphology changes under acidic and alkaline conditions well explains the trend of liquid strength changes under different pH conditions.

[0091] The fluorescence intensity of P-AB changes with pH and is reversible. The reversibility of fluorescence intensity under acidic and alkaline conditions was tested according to the following procedure. First, 3 μL of HCl solution was added to 3 ml of P-AB (CP-AB = 30 mg / L) aqueous solution, and the fluorescence spectrum was measured. Secondly, 6 μL of NaOH solution was added to the above solution, the medium was changed to an alkaline medium containing an excess of 3 μL of NaOH, and the fluorescence spectrum was measured again. Then 6 μL of HCl and 6 μL of NaOH were added alternately to the P-AB solution, and the fluorescence spectrum was measured after each addition. The results are shown in the figure. Fig.11 shown.

[0092] The results show that in each cycle, the fluorescence intensity of the solution is higher in an acidic environment and lowest in an alkaline environment. This shows that P-AB has good tolerance to both acidic and alkaline environments, and also shows that P-AB can perform fluorescence detection of solution pH.

[0093] Fluorescence phenomenon of P-AB in acidic and alkaline solutions with different ratios of water to tetrahydrofuran:

[0094] A series of acidic solutions were prepared by adding 0.15 mg of P-AB and 5 μL of HCl solution (0.5 M) to a 5 ml volumetric flask, and then supplemented with a mixture of water and THF in different proportions. Similarly, a series of alkaline solutions were prepared according to the above steps, except that the HCl solution was replaced by a hydroxide solution (5 μL, 0.5 M). The fluorescence spectra of the solutions prepared above were measured, as shown in Figure 2. Fig.12 As shown. Fig.12 B and Fig.12 D It can be found that when the proportion of THF in the solution is 0, the fluorescence intensity under acidic conditions is much greater than that under alkaline conditions, which is consistent with Figure 8 The results are in good agreement.

[0095] from Fig.12 A and Fig.12B It can be seen that under acidic conditions, when the THF ratio is from 0 to 60%, the fluorescence intensity remains high, while when the THF ratio exceeds 60%, the emission becomes weak. This means that in acidic media, even in well-dissolving solvents, strong h-bonds are generated inside or inside the polymer, thereby limiting the non-radiative channels of rotation and vibration between the BNEA fluorophores. When the THF ratio exceeds 60%, a large number of molecular chains are linked together by hydrogen bonds, and the solubility decreases. Part of the polymer precipitates from the solvent, resulting in a decrease in the fluorescence intensity of the solution.

[0096] Under alkaline conditions ( Fig.12 C and Fig.12 D), when the THF ratio is less than 40%, the fluorescence intensity increases effectively with the increase of THF ratio, and when the THF ratio is greater than 40%, the fluorescence intensity decreases slightly. This shows that P-AB has a typical AIE effect under alkaline conditions. In alkaline solutions with low THF ratios, P-AB exhibits good solubility and strong electrostatic repulsion, making the polymer chains loose and elastic. As a result, non-radiative channels of rotation and vibration are generated inside the fluorophore, introducing relatively weak emission. As the THF dosage increases, the solubility decreases and the polymer chains begin to aggregate. Therefore, with the increase of the low solvent THF content, the RIM (Restriction of molecular movement) mechanism appears, and the emission intensity increases.

[0097] Fluorescence mechanism of P-AB in acidic and alkaline solutions

[0098] Based on the above analysis of P-AB fluorescence and its TEM detection, we proposed the fluorescence mechanism of P-AB in acidic and alkaline solutions, e.g. Fig.13 As shown. In acidic solution, the active hydrogen on the carboxylic acid forms an H bond with the carbonyl group of the barbituric acid part, which restricts the rotation and vibration within the fluorophore, resulting in the AIE effect of P-AB. Therefore, the polymer P-AB emits strong fluorescence in acidic solution. In alkaline solution, the COOH on the P-AB chain becomes COO - Without active hydrogen, it is difficult to form H bonds between the P-AB chain and the fluorophore. Therefore, when the polymer is excited, the excited state may release energy in a non-radiative manner through rotation or vibration, resulting in weak emission.

[0099] Fe 3+ Effect on the fluorescence intensity of polymer P-AB:

[0100] P-AB(C) with FeCl3 concentration ranging from 0 to 176 μM was prepared. P-AB =30mg / L) aqueous solution, and measured its fluorescence spectrum, such as Fig.14As shown, the results show that the fluorescence intensity decreases significantly with the increase of FeCl3 concentration.

[0101] The fluorescence quenching of the solution may be due to the Fe 3+ It is easy to combine with -COOH, thus inhibiting the formation of H bonds between -COOH and the carbonyl group. In a good solvent, when the H bond between -COOH and the barbituric acid part is destroyed, the fluorescence intensity may decrease. 3+ The fluorescence quenching mechanism of P-AB is shown in Fig.15 .

[0102] To further confirm that Fe 3+ The fluorescence quenching mechanism of P-AB was studied by investigating the P-AB-Fe 3+ In this measurement, a series of complexes containing P-AB(C P-AB =30mg / L) and FeCl3(C FeCl3 =0.1 mM) solution, the proportion of THF ranged from 0 to 90%, and then their fluorescence spectra were measured, such as Fig.16 As shown. When the ratio of THF is 0, the fluorescence intensity is weak. When the THF ratio increases from 0 to 40%, the fluorescence intensity reaches the maximum value, and after the THF ratio is further increased, the fluorescence intensity is maintained at a high level. Fig.16 The curve in B shows that P-AB is in H2O-THF and Fe 3+ When the ratio of THF is low, P-AB dissolves well in water-THF mixture. 3+ The h-bonds around the barbituric acid moiety are suppressed, and some rotations and vibrations inside the BNEA moiety dissipate the exciton energy, resulting in weak emission at low THF ratios. As THF increases, the solubility of P-AB decreases, and P-AB begins to aggregate, limiting the rotation and vibration inside the fluorophore. This enhances the emission intensity of P-AB.

[0103] P-AB to Fe 3+ Sensing performance:

[0104] Based on Fe 3+ There is obvious fluorescence quenching of P-AB. This example studies the fluorescence response of P-AB to 17 common metal ions. A series of P-AB aqueous solutions (Ccations = 0.1 mM) containing common metal ions (Ccations = 0.1 mM) were prepared. P-AB =30mg / L). Their fluorescence spectra are as follows Fig.17 Obviously, Fe 3+ Cr 3+ and Al 3+The trivalent metal ions such as Fe and Fe show fluorescence quenching effect, while the other divalent and monovalent metal ions hardly change the fluorescence of P-AB. According to the mechanism of Scheme 3, the trivalent metal ions bind more -COOH groups than the divalent and monovalent metal ions, so the -COOH groups of the trivalent metal ions are too fixed to form H bonds. Among the three trivalent metal ions, Fe 3+ The quenching efficiency of P-AB is the highest.

[0105] P-AB to Fe 3+ Stern-Volmer quenching constant and detection limit (DL):

[0106] from Fig.18 It can be seen that the fluorescence intensity of the solution increases with the Fe 3+ The concentration of Fe 3+ When the concentration was 112 μM, the fluorescence disappeared completely. Fig.18 It can be seen that when Fe 3+ When the concentration is in the range of 0 to 112 μM, the detection of P-AB has a good linear relationship and can be used as a Fe 3+ The quantitative detection sensor has a detection limit of 46.48μM.

[0107] Interference from common cations:

[0108] In order to understand the effects of other cations on Fe 3+ The interference of detection, in the presence of P-AB and Fe 3+ 16 other cations were added to the aqueous solution. Fig.19 In A, compared with the blank solution, the addition of Fe 3+ The fluorescence of all solutions was quenched. This indicates that other cations act on Fe 3+ There is no interference in the detection. Fig.19 In B, the Fe-containing 3+ Solution and Fe-free 3+ Clear contrast in fluorescence intensity between solutions.

[0109] Effect of pH value on the fluorescence intensity of P-AB and Fe3+ complex:

[0110] P-AB and Fe at different pH values 3+ Fluorescence intensity was detected in aqueous solution. Fig. 20 As shown. Obviously, the pH value in the range of 3 to 11 has no significant effect on the fluorescence intensity. However, when the pH reaches 12, the fluorescence intensity of the solution suddenly increases. This is because in a strong alkaline environment, the Fe 3+It combines with hydroxide to form a precipitate and no longer combines with carboxylic acid. Therefore, P-AB can be used to detect Fe in aqueous solutions with a pH value below 11 3+ .

[0111] With or without Fe 3+ Fluorescence stability of P-AB:

[0112] Measuring the fluorescence stability of probe P-AB in aqueous solution ( Fig.21 A). This measurement studies the fluorescence intensity at an excitation wavelength of 550 nm and an emission wavelength of 610 nm. The fluorescence intensity of P-AB hardly changes within 20 min. This indicates that P-AB has good photostability in aqueous solution.

[0113] Test Fe 3+ Response time to P-AB, such as Fig.21 B. Add Fe to the P-AB aqueous solution 3+ After the reaction, the fluorescence intensity of the solution decreased immediately. The fluorescence of P-AB was almost completely quenched within 40 seconds. This phenomenon indicates that the probe P-AB has a strong affinity for Fe in aqueous solution. 3+ Respond quickly.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A barbituric acid-based polyacrylic acid derivative, characterized in that: Its chemical structure is shown below: Among them, m=1~100, n=50~400, m:n=1:2~10.

2. The barbituric acid-based polyacrylic acid derivative according to claim 1, wherein m is: n=1:4~8。 3. The barbituric acid-based polyacrylic acid derivative according to claim 1, characterized in that: The weight average molecular weight is (1.0~5.0)×10 4 .

4. A method for preparing a barbituric acid-based polyacrylic acid derivative according to claim 1, characterized in that: The monomer BNEA is obtained by double bond polymerization reaction with acrylic acid; the chemical structure of the monomer BNEA is as follows: The molar ratio of monomer BNEA to acrylic acid is 1:2-10; The initiator used in the double bond polymerization reaction is azobisisobutyronitrile; The conditions for the double bond polymerization reaction are: heating to 65-80° C. under an inert atmosphere.

5. The method for preparing a barbituric acid-based polyacrylic acid derivative according to claim 4, wherein: The molar ratio of the monomer BNEA to acrylic acid is 1:4-8.

6. Use of the barbituric acid-based polyacrylic acid derivative according to any one of claims 1 to 3 in fluorescence detection of pH.

7. The use of the barbituric acid-based polyacrylic acid derivative in fluorescence detection of pH as claimed in claim 6, characterized in that: The barbituric acid-based polyacrylic acid derivative is added into the aqueous solution to be tested for fluorescence detection.

8. A barbituric acid-based polyacrylic acid derivative according to any one of claims 1 to 3 for detecting Fe in fluorescence 3+ Application in.

9. The barbituric acid-based polyacrylic acid derivative according to claim 8 is used for the fluorescence detection of Fe 3+ The application is characterized by: The pH value of the solution is not higher than 11.

10. A method for detecting Fe 3+ The device is characterized in that The invention comprises the barbituric acid-based polyacrylic acid derivative according to any one of claims 1 to 3 and a fluorescence spectrometer, wherein the fluorescence spectrometer is used to detect the fluorescence of the barbituric acid-based polyacrylic acid derivative after mixing with an aqueous solution to be tested.

Citation Information

Patent Citations

  • Application of thiobarbituric acid structure compound in preparation of photoinitiator

    CN117586437A

  • Compound containing barbital structure as well as preparation method and application of compound

    CN117624062A